Coordinating Lifesaving Product Development Projects with no Preestablished Organizational Governance Structure - Barbosa, Ana Paula Paes Leme; Facin, Ana Lucia Figueiredo [UNESP]; Salerno, Mario Sergio; Freitas, Jonathan Simões; Reis, Marina Carelli; Lasmar, Tiago Paz (SAGE Publications, 2022)
We employed a longitudinal, grounded theory approach to investigate the management of an innovative product developed in the context of a life-or-death global emergency. This project involved about 40 multidisciplinary researchers, multisector companies, and open-source collaboration. Inductively, we identified the emergence and evolution of project coordination approaches, roles, and the project network along with the project's life cycle. The present study shows how configurations of these elements coevolve as the project moves forward with no predefined structures or procedures. Therefore, it provides insights for coordinating innovative projects in the face of extreme time constraints and ill-defined institutional frameworks.
Keywords: coordination; governance; innovative project; pandemic